Mies van der Rohe : the built work - Krohn, Carsten (Birkhäuser, 2014)
This essential and comprehensive Mies monograph focuses in its analysis on Mies' design intentions: it reconstructs the buildings in their orginal state, examines them from the present day persepctive and rediscovers the inspiring architecture of a great modern master. The book presents eighty of Mies' works in chronological order.